1997
DOI: 10.1046/j.1365-2168.1997.02760.x
|View full text |Cite
|
Sign up to set email alerts
|

Colour duplex scanning and pulse-generated run-off for assessment of popliteal and cruropedal arteries before peripheral bypass surgery

Abstract: Operative strategy could have been based on investigation by duplex scanning and PGR in a substantial number of patients scheduled for femoropopliteal bypass surgery. Agreement between duplex scanning and IADSA within very distal arterial segments was fair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Caster et al reported a success rate of 94, 96 and 83 % for the anterior tibial, posterior tibial and peroneal arteries, respectively [48]. As confirmed in many studies, the peroneal artery needed a more laborious examination due to its deep location and the surrounding fascial borders [46, 49,50]. Data are difficult to compare because the aims of different studies showed some variation.…”
Section: Accuracy Of Colour Doppler In the Detection Of Stenoses And mentioning
confidence: 94%
See 1 more Smart Citation
“…Caster et al reported a success rate of 94, 96 and 83 % for the anterior tibial, posterior tibial and peroneal arteries, respectively [48]. As confirmed in many studies, the peroneal artery needed a more laborious examination due to its deep location and the surrounding fascial borders [46, 49,50]. Data are difficult to compare because the aims of different studies showed some variation.…”
Section: Accuracy Of Colour Doppler In the Detection Of Stenoses And mentioning
confidence: 94%
“…11). A technically adequate examination was reported to be feasible in 80±100 % of cases, taking into account that careful exploration of distal vessels is a time-consuming investigation (from 10 to 90 min) [10,11,41,43,46,47,48,49,50,51,52]. Caster et al reported a success rate of 94, 96 and 83 % for the anterior tibial, posterior tibial and peroneal arteries, respectively [48].…”
Section: Accuracy Of Colour Doppler In the Detection Of Stenoses And mentioning
confidence: 99%
“…The studies comparing duplex imaging with DSA in the assessment of the cruropedal arteries report widely divergent results (Karacagil et al 1996;Koelemay et al 1997) with sensitivities and specificities for the detection of occlusion ranging from 50% to 90%. However, the investigators used 5 MHz transducers, which are inadequate for the pedal vessels, and the low resolution may explain the poor results.…”
Section: )mentioning
confidence: 99%
“…Provided that the ultrasonographers who are performing the examination are highly experienced, duplex US has very good results for sensitivity and specificity, even with regard to the depiction of the lower legs (25)(26)(27). Similarly, the image quality of MR angiography depends on the quality of the equipment and the experience of the MR technologists.…”
Section: Discussionmentioning
confidence: 95%